The Impact of an Online Cultural Simulation Activity on the Development of Speech Pathology Students’ Cultural Empathy: A Pilot Study: A pilot study - Hewat, Sally; Walters, Joanne; Lee, Monica (International Journal of Practice-based Learning in Health and Social Care, 2020)
Despite the cultural and linguistic diversity of the Australian population, research suggests that speech pathologists do not feel confident when providing services to Cultural and Linguistic Diversity (CALD) clients and would benefit from further education and training in this area. Cultural empathy has been described as a precursor to cultural competence and previous research has demonstrated the positive impact on nursing students’ cultural empathy toward CALD clients following an interactive cultural simulation experience. This study investigated the feasibility and effectiveness of an online cultural simulation activity in developing the cultural empathy of speech pathology students. Students completed an online cultural simulation in their own time, followed by a tutorial debrief. Both the simulation and debrief were considered to comprise the ‘simulation activity’; which was a component of a first-year introduction to clinical practice course. Participants completed a pre-survey and post-survey, containing the Comprehensive Empathy Scale (CES) and demographic questions. Results were analysed using the Wilcoxon Signed Rank test and a Paired Sample t-test, and a power analysis was conducted to direct future studies. Ten students participated and improved an average of 11.3 on the CES (p=0.14). A power analysis revealed that a minimum of 45 participants would be needed in future studies to observe any statistically significant results. The online application of the cultural simulation activity was feasible, and results indicate an improvement in cultural empathy, although the improvement did not reach statistical significance. Implications for future studies are discussed.